WEE1 Dependency and Pejorative Prognostic Value in Triple‐Negative Breast Cancer. Issue 17 (6th July 2021) - de Nonneville, Alexandre; Finetti, Pascal; Birnbaum, Daniel; Mamessier, Emilie; Bertucci, François
Abstract : The WEE1 G2 checkpoint kinase acts as a negative cell cycle regulator for entry into mitosis (G2‐to‐M transition). This comment extends a recent Advanced Science paper by reporting higher WEE1‐dependency of triple negative breast cancer (TNBC) cell lines, pejorative prognostic value of WEE1 expression in TNBC clinical samples as well as higher expression of biomarkers of sensitivity to WEE1 inhibitor.